Amil Zakat Institutions Performance Analysis During the Covid-19 Pandemic: Studies in Indonesia, Singapore, and England - Abd. Akram H; Tettet Fitrijanti; Dini Rosdini (Journal of Islamic Economics Lariba, 2022)
The Amil Zakat Institution is required to have efficient and effective performance, especially during the Covid-19 health crisis. This study aims to measure the performance of amil zakat institutions in Indonesia, Singapore, and England based on the efficiency level with the Data Envelopment Analysis approach and the level of effectiveness with the Allocation to Collection Ratio approach. The efficiency level of amil institutions was measured using the Data Envelopment Analysis method, the non-parametric statistical approach used in calculating the relativity of efficiency. The software used to measure Data Envelopment Analysis is DEAP 2.1. The results of efficiency measurements based on the Data Envelopment Analysis showed that Dompet Dhuafa, Majlis Ugama Islam Singapore (MUIS), and the National Zakat Foundation (NZF) achieved optimal and efficient performance during the Covid-19 pandemic (in 2020), but experienced inefficiency before the Covid-19 pandemic in 2017 (Dompet Dhuafa), 2018 (Dompet Dhuafa & NZF), and 2019 (MUIS). If assessed based on effectiveness in channeling funds using the Allocation to Collection Ratio, Dompet Dhuafa, Majlis Ugama Islam Singapore, and the National Zakat Foundation achieved effective values ​​both before and during the Covid-19 pandemic.